Multinational corporations and tax havens: Evidence from country-by-country reporting - Javier Garcia-Bernardo; Petr Janský; Thomas Tørsløv (Charles University in Prague, Institute of Economic Studies (IES), 2019)
A growing body of economics literature shows that multinational corporations (MNCs) shift their profits to tax havens. We contribute to this evidence by comparing a range of available data sets focusing on US MNCs, including country-by-country reporting data which has been released in December 2018 for the first time. With each of the datasets, we analyse the effective tax rates that US MNCs face in each country and the amount of profits they report. Using country-by-country reporting data, we have been able to establish that lower effective corporate tax rates are associated with higher levels of reported profits when compared with different indicators of real economic activity. This corresponds to the notion that MNCs often shift profits to countries with low effective tax rates - without also shifting substantive economic activity. Consequently, we identify the most important tax havens for US MNCs as countries with both low effective tax rates and high profits misaligned with economic activity.
Keywords: C81; F21; F23; H25; H26; 330; Effective tax rate; profit shifting; tax haven; country-by-country reporting; multinational enterprise; foreign direct investment; tax competition